A formação nos cursos de fisioterapia na Paraíba para a atuação na atenção básica à saúde - Lucena, Eleazar Marinho de Freitas (2018)
Considering Brazilian population’s new health demands, due to major changes in social arrangement, epidemiological framework and health system organization, it is necessary to reformulate physiotherapy intervention object, which needs to approach health promotion and the new perspective in terms of care structures, without being detached from its inherent skills in rehabilitation. Therefore, the thesis is defended that professional training is not preparing physiotherapists to act in primary health care scope. Thus, this study aims to investigate undergraduate students in Physiotherapy’s professional training process in Paraíba (Brazil) to perform primary health care. It is an exploratory, descriptive and inferential study with qualitative and quantitative approaches. Research was carried out in Higher Education Institutions (HEI) of Paraíba which offer undergraduate course in Physiotherapy. Professional training for primary care was investigated from students’ and teachers’ perspective, through semi-structured interviews. Students’ knowledge about basic health care training was evaluated through the application of a questionnaire based on National Basic Attention Policy (PNAB, in Portuguese) and Basic Attention Manual No. 39 of the Family Health Support Center (NASF, in Portuguese). Qualitative data were analyzed using Content Analysis technique, while quantitative data were analyzed using Item Response Theory (IRT) statistical technique. Physiotherapy courses’ students from Paraíba value the experiences realized in primary health care during their formation. However, they recognize that the focus is on rehabilitation actions, limiting physiotherapist’s action possibilities. According to the students, opportunities occurred late and punctual during the course, which leaded to a certain theoretical limitation and difficulty in developing skills to perform at this attention level due to the short action time, evidencing the need for disciplines with a focus on primary care as important for physiotherapist’s training. When it comes to guiding documents’ content, a restricted understanding is observed. This reveals that physiotherapist’s training still does not fully contemplate basic care and NASF assumptions. Professors highlighted as unfavorable aspects of this training insufficient workload, teaching fragmentation and the difficulty to integrate what is studied in this attention level with other curricular components. Therefore, it is necessary to adapt undergraduate courses’ curricular structure, in order to optimize curricular components’ workload inherent to this attention level, interdisciplinarity and teaching-service integration. This study allowed to elaborate an instrument to analyze students’ Physiotherapy knowledge about primary health care aspects. Considering the findings in this study, it can be perceived that subjects in undergraduate courses in Physiotherapy from Paraíba are not prepared to act in primary health care in guiding documents’ context.